1984
DOI: 10.1007/bf02408556
|View full text |Cite
|
Sign up to set email alerts
|

Tourette syndrome: A review and educational implications

Abstract: Tourette syndrome has recently been brought to public attention through popular media. This review of the literature is an effort to communicate to special educators and allied professionals in nonmedical terms the present state of the art with regard to the definition, symptoms, etiology, treatment, and educational implications of Tourette. The review is concluded with suggestions for the education of Tourette students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

1987
1987
2008
2008

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Researchers, in addition, have found that children with ADHD perform poorly on arithmetic tests and that, when their attentional problems are treated with stimulant medication, their math performance improves (BenedettoNasho & Tannock, 1999;Swanson et al, 1998). Other authors implicitly acknowledge the importance of attention by recommending the addition of structure within the classroom as a compensatory means for improving arithmetic performance in students with TS (Bauer & Shea, 1984;Harcherick, Carbonari, Shaywitz, Shaywitz, & Cohen, 1982).…”
Section: Introductionmentioning
confidence: 92%
“…Researchers, in addition, have found that children with ADHD perform poorly on arithmetic tests and that, when their attentional problems are treated with stimulant medication, their math performance improves (BenedettoNasho & Tannock, 1999;Swanson et al, 1998). Other authors implicitly acknowledge the importance of attention by recommending the addition of structure within the classroom as a compensatory means for improving arithmetic performance in students with TS (Bauer & Shea, 1984;Harcherick, Carbonari, Shaywitz, Shaywitz, & Cohen, 1982).…”
Section: Introductionmentioning
confidence: 92%
“…cent advances, there is a clear need for data that can guide the daily management and educational programs of these children (Bauer & Shea, 1984). A necessary step in developing appropriate educational and management strategies with TS children is the identification of their intellectual, academic, and adaptive strengths and weaknesses.…”
mentioning
confidence: 99%
“…There is some evidence that education apparently decreases misunderstanding by teachers and teasing by peers (Comings & Comings, 1987;Levi, 1991). Moreover, Bauer and Shea (1984), in a comprehensive review of TS research and its educational implications, concluded that a focus on empathy, acceptance, and friendship with regard to the individual with TS in the classroom is crucial to promoting positive social interactions.…”
mentioning
confidence: 99%